Biology and ecology of venomous marine scorpionfishes - Santhanam, Ramasamy, 1946- (Academic Press, 2018)
Biology and Ecology of Venomous Marine Scorpionfishes examines the diversity, utilization, and ways to safeguard against the world's most dangerous fish species. It covers the biological and ecological factors that differentiate each species in the Scorpaeninae (Scorpionfish) family and its Pteroinae (Lionfish) subfamily. This book offers important anatomical and identification information on marine scorpionfishes and delves into the diversity, habits and behaviors of each venomous species. In addition, it discusses the health risks that can plague these fish in and out of the wild, including parasites. This book is an essential resource to educate marine biology researchers and students on the various species of scorpionfish that also provides sea-goers with a guide that will help protect them against venomous stings from these fish.